2015
DOI: 10.1371/journal.pone.0118924
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Noun Processing: An ERP Study with Rapid Serial Visual Presentation

Abstract: Reading is an important part of our daily life, and rapid responses to emotional words have received a great deal of research interest. Our study employed rapid serial visual presentation to detect the time course of emotional noun processing using event-related potentials. We performed a dual-task experiment, where subjects were required to judge whether a given number was odd or even, and the category into which each emotional noun fit. In terms of P1, we found that there was no negativity bias for emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…The recent study performed by Zhang et al verified markedly the modulation of LPC by emotional adjectives, reflecting the larger LPC amplitudes elicited by positive words than the ones by negative words and neutral words [ 116 ]. The results are consistent with the previous studies and a subsequent study using emotional nouns [ 131 , 150 , 161 163 ]. For emotional faces, Calvo et al equally analyzed the LPP response to emotional faces, but the emotion modulation of the component was only seen in upper face half condition with an augmented LPP amplitudes for angry faces than those for the other expressions (neutral, happy, and surprise) [ 146 ].…”
Section: Emotion Processing Revealed By Erpssupporting
confidence: 93%
“…The recent study performed by Zhang et al verified markedly the modulation of LPC by emotional adjectives, reflecting the larger LPC amplitudes elicited by positive words than the ones by negative words and neutral words [ 116 ]. The results are consistent with the previous studies and a subsequent study using emotional nouns [ 131 , 150 , 161 163 ]. For emotional faces, Calvo et al equally analyzed the LPP response to emotional faces, but the emotion modulation of the component was only seen in upper face half condition with an augmented LPP amplitudes for angry faces than those for the other expressions (neutral, happy, and surprise) [ 146 ].…”
Section: Emotion Processing Revealed By Erpssupporting
confidence: 93%
“…However, there are also processing differences between the two stimulus types. Firstly, we found that negative expressions and adjectives elicited lager right ( Luo et al, 2010 ) and left ( Zhang et al, 2014 ) N1 amplitudes, respectively, than did positive and neutral expressions and adjectives; however, the N1 amplitudes elicited by negative, neutral, and positive nouns were not significantly different ( Yi et al, 2015 ). Secondly, although the N170 effect has been found in all processes, the right hemisphere appears to be superior for processing emotional facial expressions, but the left hemisphere appears to be superior for word (both emotional adjective and noun) processing.…”
Section: Introductionmentioning
confidence: 79%
“…Additionally, previous studies ( Chun, 1997 ; Kessler et al, 2005 ; Shapiro et al, 2006 ) revealed that the attentional resources and task difficulty were affected by two factors, the inter-stimulus interval (the attentional blink appeared when the inter-stimulus interval ranged from 200 to 500 ms) and the number of tasks (participants perform better on a single-task than on a dual-task, which is referred to as the attentional blink), especially in the middle and late stage of emotion processing (for details, please refer to our previous work). The three-stage model of emotional facial expressions and words processing proposed in our previous studies ( Luo et al, 2010 ; Zhang et al, 2014 ; Yi et al, 2015 ), was based on the lack of attentional resources, i.e., a process is in accordance with the three-stage model only when the processing of emotional facial expressions and words is within the attentional blink time window. The present study aimed to test whether the processing of emotional pictures other than faces is also in line, or partly in line, with the three-stage model; therefore, the test needed to be conducted under conditions where the participants lacked attentional resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some research findings have preliminarily reported the time course of neural dynamics of emotional stimuli, using the event-related potential technique, which indicated that the neural processing of emotional adjectives also consisted of three stages (i.e., automatic processing, distinguishing emotional and neutral information, and emotion separation, successively; Zhang et al, 2014a), which is similar with facial expressions (Luo et al, 2010), emotional pictures (Zhu et al, 2015), and nouns (Yi et al, 2015). This similarity inherently centers around a fundamental fact that the resulting distributions of various emotional materials share an underlying two-dimensional affective space (Bradley and Lang, 1999; Bradley et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%